Ricky ricotta's mighty robot vs. the mecha-monkeys from mars ebook - Pilkey, Dav (Ricky Ricotta, 2014)
From Dav Pilkey, the worldwide bestselling author-illustrator of Dog Man, and award-winning illustrator Dan Santat comes an out-of-this-world friendship adventure in full color! Best friends always stick together — especially when they are in trouble! Ricky Ricotta and his Mighty Robot always watch out for each other — that's what friends are for! This time, they've managed to mangle the Ricotta family's minivan. Somehow they have to find a way to make up for their mistake. When a mean little Martian named Major Monkey invades Earth, Ricky and his Robot race to save the day once more. But Major Monkey has a plan to get rid of Ricky's Robot so that no one will be able to stop him! Now it's up to Ricky to rescue his friend and keep Major Monkey from menacing mousekind!